Limno-geographical characteristics of Sarua Lake, Gorakhpur, India - Alka Singh; Vishwambhar Nath Sharma (National Geographical Journal of India, 2022)
Lakes have immense ecological, social, cultural and economic value, but eutrophication and siltation in the lake, reduction in area, and depleted water quality have led to a significant deterioration of the lake. This study found the cause-effect relationship between the increasing anthropogenic actions on lake beds to know about the status of lake ecology through limno-geogarphical studies. This study analyzed the spatio-temporal distribution of fifty years, ten types of utility, limno-geographical characteristics (area, average depth, circumference, volume, maximum length, and width), physical quality (EC, pH, TDS, water colour) of lake water lake ecology (TSI), causes and consequences of the deterioration of lake, and stewardship of Sarua Lake in the Gorakhpur district. The ecology of Sarua lake is eutrophic based on Secchi depth due to enter of surface runoff, agricultural runoff which came with a huge amount of nitrate and phosphate and increase the productivity in bottom deposits materials and flourished the immense coverage of littoral plants. The extent of Sarua lake is reduced by 1.65 kilometres squares within 50 years and the average depth decreased by 33 percent within 30 years due to the entry of natural surface runoff and the impact of anthropogenic activities (expansion of human habitat, entering of sewage, expansion of agricultural runoff, reduction of lake extent). These anthropogenic activities generated some opportunities and threats to local livelihoods and altered the social action which was dependent on lake beds from a very primitive time.